Implementasi Algoritma Turbo Boyer Moore Pada Aplikasi Pengobatan dengan Rempah-Rempahan Berbasis Android - Meijini Lucy Neory (STMIK Budi Darma, 2020)
Spices are parts of plants that are aromatic. A flavorful or strong-flavored plant part spice used in small edible quantities as a preservative or flavoring in food. At this time treatment is not only done medically, but can also be done traditionally. However, the problem that occurs with traditional medicine is the lack of existing books that discuss traditional medicine and the lack of information on the internet that discusses traditional medicine, making people prefer medical treatment which of course requires a large cost. The Android-Based Spices Medicine Application is made with the Turbo Boyer Moore Algorithm. Boyer Moore's Turbo algorithm is a variation of the Boyer Moore algorithm. Turbo Boyer Moore has two advantages, namely that it allows to skip the factor of the text and the moore's turbo boyer technique allows turbo shifting.